The roles and potential mechanisms of plant polysaccharides in liver diseases: a review - Wei, Xianzhi; Luo, Daimin; Li, Haonan; Li, Yagang; Cen, Shizhuo; Huang, Min; Jiang, Xianxing; Zhong, Guoping; Zeng, Weiwei (Frontiers in Pharmacology, 2024)
Plant polysaccharides (PP) demonstrate a diverse array of biological and pharmacological properties. This comprehensive review aims to compile and present the multifaceted roles and underlying mechanisms of plant polysaccharides in various liver diseases. These diseases include non-alcoholic fatty liver disease (NAFLD), alcoholic liver disease (ALD), fibrosis, drug-induced liver injuries (DILI), and hepatocellular carcinoma (HCC). This study aims to elucidate the intricate mechanisms and therapeutic potential of plant polysaccharides, shedding light on their significance and potential applications in the management and potential prevention of these liver conditions. An exhaustive literature search was conducted for this study, utilizing prominent databases such as PubMed, Web of Science, and CNKI. The search criteria focused on the formula "(plant polysaccharides liver disease) NOT (review)" was employed to ensure the inclusion of original research articles up to the year 2023.Relevant literature was extracted and analyzed from these databases. Plant polysaccharides exhibit promising pharmacological properties, particularly in the regulation of glucose and lipid metabolism and their anti-inflammatory and immunomodulatory effects. The ongoing progress of studies on the molecular mechanisms associated with polysaccharides will offer novel therapeutic strategies for the treatment of chronic liver diseases (CLDs).